Case report: Influenza A virus and Human herpesvirus 1 infection-associated acute encephalopathy in children with the mutations in the SLC25A19 andTICAM1 gene, respectively - Ni, Jingwen; Fang, Boliang; Xu, Huan; Liu, Yahui; Fang, Kenan; Li, Shujun (IDCases, 2023)
Infection-associated acute encephalopathy (AE) is a clinical condition caused by a variety of pathogens, particularly common viruses. In some cases, this condition could be characterized by a sudden onset and a rapid progression, leading to severe neurological sequelae, including acute encephalopathy with biphasic seizures and late reduced diffusion, hemorrhagic shock and encephalopathy syndrome, etc.BackgroundInfection-associated acute encephalopathy (AE) is a clinical condition caused by a variety of pathogens, particularly common viruses. In some cases, this condition could be characterized by a sudden onset and a rapid progression, leading to severe neurological sequelae, including acute encephalopathy with biphasic seizures and late reduced diffusion, hemorrhagic shock and encephalopathy syndrome, etc.In this study, it was reported that three previously healthy children developed acute encephalopathy/encephalitis symptoms with different neurological sequelae after either Influenza A Virus or Human Herpesvirus 1 infection, presenting with fever and convulsions. What's more, after performing the gene exon detection for these three children, it was found that there are abnormal genes corresponding to their neurological sequelae, including SLC25A19 and TICAM1.Case presentationIn this study, it was reported that three previously healthy children developed acute encephalopathy/encephalitis symptoms with different neurological sequelae after either Influenza A Virus or Human Herpesvirus 1 infection, presenting with fever and convulsions. What's more, after performing the gene exon detection for these three children, it was found that there are abnormal genes corresponding to their neurological sequelae, including SLC25A19 and TICAM1.Therefore, comparing to children with common encephalitis, for children with encephalitis whose progression is rapid and clinical manifestations such as recurrent fever and frequent convulsions is difficult to improve, whole-exome sequencing can be a valuable tool for identifying encephalitis-associated genetic variants and providing strong evidence for prognostic prediction.ConclusionsTherefore, comparing to children with common encephalitis, for children with encephalitis whose progression is rapid and clinical manifestations such as recurrent fever and frequent convulsions is difficult to improve, whole-exome sequencing can be a valuable tool for identifying encephalitis-associated genetic variants and providing strong evidence for prognostic prediction.